2018
DOI: 10.1111/jfpp.13767
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of beef mixtures adulterated with chicken or turkey meat using FTIR spectroscopy

Abstract: Fourier transform infrared (FTIR) spectroscopy was used as a tool to identify adulterated beef in raw meat mixtures, incorporating chicken or turkey meat in different proportions, 0%, 5%, 10%, 20%, 40%, and 100%. Six regions with characteristic bands were determined where significant differences were observed depending on the proportion of the substitution. In hierarchical cluster analysis (HCA), dendrograms for wavenumbers between 2,980–2,800 cm−1 and 1,140–1,020 cm−1 provided effective differentiation for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The absolute intensity values for these peaks showed a decrease (p<0.05) with higher ratios of adulterant meats (pork, horse and donkey). It is noteworthy to mention that peak 9 was only detected in the spectra of beef samples, which was also previously reported by Deniz et al 2018, but not observed in the spectra of 100% meat from pork, donkey or horse. Two peaks at 1115 and 1096 cm -1 wavenumbers were detected in beef samples in region 6 which were attributed to different nature and composition of lipids which might result from stretching vibrations of C\O in triacylglycerols (Kurniawati et al, 2014), C-H bending vibration and C-H deformation vibrations of fatty acids, respectively (Rohman et al, 2011).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The absolute intensity values for these peaks showed a decrease (p<0.05) with higher ratios of adulterant meats (pork, horse and donkey). It is noteworthy to mention that peak 9 was only detected in the spectra of beef samples, which was also previously reported by Deniz et al 2018, but not observed in the spectra of 100% meat from pork, donkey or horse. Two peaks at 1115 and 1096 cm -1 wavenumbers were detected in beef samples in region 6 which were attributed to different nature and composition of lipids which might result from stretching vibrations of C\O in triacylglycerols (Kurniawati et al, 2014), C-H bending vibration and C-H deformation vibrations of fatty acids, respectively (Rohman et al, 2011).…”
Section: Resultssupporting
confidence: 82%
“…This is a clear indication that the present study with zoomed view provided considerable distinction of the specific peaks from beef as well as from other mixtures in terms of intensity values. One shoulder peak at 1728 cm -1 (S1) in region 2 was observed only for the mixtures containing beef (Figure 1) where intensities were greater with increasing content of beef in the mixtures, indicating that this shoulder is characteristic for beef samples (Deniz et al 2018). Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations